Direk yabancı yatırımların Kırgızistan’a gelmesinin belirleyicileri - İbraimova, Gülnur (My University, 2005)
In this study; firstly, some theoric points about the direct foreign investments are dealt with; and the direct foreign invesments made throughout Kirghizistan and their determiners are pointed out. In the First Section of the Study, the definition and classification of direct foreign investments are made, and their importance is mentioned. The reasons that canalize the institutions into direct universal investments and some main developments are tried to be explained. In the second section; the investment atmosphere of Kırghizistan is studied. Information about the National Investment Policy of Kırghizistan is given; its targets and duties are explained. The fields where the investment policy of the country are applied, are also satated. The laws and regulations regarding the direct foreign investments for the country are emphasized. On dealing with the atmosphere of the investments; the dispersion of these direct foreign investments among the financial sectors and regions is explained. Besides; the countries from which these investment flows come and the companies operating in these countries are also stated. In the last section of the study; the factors affecting the foreign investments throughout the country and the reasons causing the foreign investers to decide to invest their capitals in Kirghizistan are tried to be investigated and evaluated.

Bu çalışmada öncelikle direk yabancı yatımlarla ilgili teorik bilgilere değinilmiş ve Kırgızistan’a yapılan direk yabansı yatırımlar ve onların belirleyicileri üzerinde durulmuştur. Çakışmanın Birinci Bölümünde direk yabancı sermaye yatırımların tanımı, önemi ve sınıflandırması yapılarak, işletmeleri uluslararası direk yatımlara yönelten nedenler ve başlıca yeni gelişmeler açıklanmaya çalışılmıştır. İkinci bölümde Kırgızistan’ın yatırım ortamı incelenmiştir. Kırgızistan’ın Ulusal Yatırım Politikası hakkında bilgi verilerek, amaç ve görevleri anlatılmıştır. Ülkenin yatırım politikasının uygulandığı alanlara da yer verilmiştir. Ayrıca ülkedeki direk yabancı yatırımlar için gerekli olan kanun ve mevzuatlar açıklanmıştır. Kırgızistan’daki yatırım ortamı incelenerek, direk yabancı yatırımların ekonomi sektörlerine ve bölgelere göre dağılımı anlatılmakta ve bununla birlikte yatırım akımlarının geldiği ülkeler ve ülkede faaliyette bulunan şirketlere yer verilmiştir. Çalışmanın son kısmında ise, yabancı yatırımcıların Kırgızistan’a sermayelerini yatırmaya karar vermesini ve ülkede bulunan yabancı yatırımların etkileyen faktörlerin neler olduğunu araştırılmaya ve değerlendirmeye çalışılmıştır.
Keywords: Ekonomi_Kırgızistan; Yatırımlar, Yabancı